1998
DOI: 10.1136/jcp.51.6.427
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase immunoreactivity in early gestation and in trophoblastic disease.

Abstract: Aims-To study the localisation of the endothelial nitric oxide synthase (eNOS) in the normal placenta, with special emphasis on the implantation site in the first trimester of pregnancy, and in the diVerent subtypes of trophoblastic cells in gestational trophoblastic disease. Methods-The immunoperoxidase technique with an antibody directed against eNOS was applied to paraYn sections from first and second trimester placentas, placenta accreta, partial and complete hydatidiform moles, and choriocarcinoma. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…In rodents, Saxena et al reported up-regulation of iNOS in implantation site [46] and Fuhrmann et al demonstrated the importance of the combination of iNOS and progesterone in implantation [47]. By contrast, Ariel et al identified eNOS immunoreactiviry in the human extravillous trophoblastic cells, suggesting the possible involvement of eNOS in human implantation [48]. Thus, the physiological role of iNOS as well as eNOS in the chorionic villous tissues in the first trimester is still obscure in humans [49].…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, Saxena et al reported up-regulation of iNOS in implantation site [46] and Fuhrmann et al demonstrated the importance of the combination of iNOS and progesterone in implantation [47]. By contrast, Ariel et al identified eNOS immunoreactiviry in the human extravillous trophoblastic cells, suggesting the possible involvement of eNOS in human implantation [48]. Thus, the physiological role of iNOS as well as eNOS in the chorionic villous tissues in the first trimester is still obscure in humans [49].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial NOS is expressed in the fetal placenta from early pregnancy in several species (Sladek et al 1997, Ariel et al 1998, Gagioti et al 2000, Al-Hijji et al 2003. NOS are recognized as regulators of implantation and pregnancy maintenance, and angiogenesis in the fetal and maternal placenta (Gagioti et al 2000, Maul et al 2003; however, the mechanism of NOS effects on these processes remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In humans there are scant data on the specific role of NO in embryo development, decidual transformation, and embryo implantation. However, indirect evidences confirm that, depending on its concentrations, NO can both inhibit or stimulate embryonic development and implantation (28,29).…”
Section: Discussionmentioning
confidence: 99%